John Adams [videorecording (DVD)] - Hooper, Tom, 1972-; Giamatti, Paul; Linney, Laura; Dillane, Stephen, 1956-; McCullough, David G. (HBO Video, 2008)
While our new nation was suffering attacks from both within and without, John Adams had a vision of a nation of liberty and justice for all. He guided his peers--General George Washington, Benjamin Franklin and Thomas Jefferson--in setting the values and agenda for a glorious, free America. Adams and his wife Abigail refined these ambitious democratic ideals, and their partnership became one of the most moving love stories in American history.